Interaction and connectivity in the Greater Southwest - Harry, Karen G., editor; Roth, Barbara J., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
Exploring different kinds of social interaction that occurred prehistorically across the Southwest by using innovative approaches and different data sets to examine the economic, social, and ideological implications of different forms of interaction and presenting new ways to examine how social interaction and connectivity influenced cultural developments.--Provided by publisher.
Interaction and connectivity in the Greater Southwest: introduction / Karen G. Harry and Barbara J. Roth -- Beyond trade and exchange: a new look at diffusion / Catherine M. Cameron -- Reframing diffusion through social network theory / Barbara J. Mills and Matthew A. Peeples -- There and back again / Kelley A. Hays-Gilpin, Dennis A. Gilpin, Suzanne L. Eckert, John A. Ware, David A. Phillips, Jr., Hayward H. Franklin, and Jean H. Ballagh -- The diffusion of scarlet macaws and Mesoamerican motifs into the Mimbres region / Patricia A. Gilman, Marc Thompson, and Kristina C. Wyckoff -- Maintenance, revival, or hybridization?: distinguishing between types of identity reconstruction in the American Southwest / Suzanne L. Eckert -- Identifying social units and social interaction during the Pithouse period in the Mimbres region, southwestern New Mexico / Barbara J. Roth -- House variability during the PIII period in the Kayenta region of the American Southwest / Tammy Stone -- Jornada formative settlements in the highlands and lowlands: contrasting paths to Pueblo villages / Thomas R. Rocek -- Identifying nested social groups: the Pioneer period in the Tucson Basin / Eric Eugene Klucas and William M. Graves -- Household ritual and communal ritual: kivas and the making of community in the southern Chuska Valley / John G. Douglass, William M. Graves, David T. Unruh, Phillip O. Leckman, and Richard Ciolek-Torello -- The social dimensions of prehistoric Agavaceae baking pits: feasting and leadership in the late Pithouse and Pueblo periods of south-central New Mexico / Myles R. Miller -- The Northern Frontier in the history of the Greater Southwest / James R. Allison -- Changing patterns of interaction and identity in the Moapa Valley of southern Nevada / Karen G. Harry -- Prehistoric hunter-gatherer-farmer identities in Las Vegas Valley, southern Nevada / Richard V.N. Ahlstrom -- The Jackson Flat Reservoir project: examples of culture change at a Virgin Branch settlement in Kanab, Utah / Heidi Roberts -- The late Fremont regional system / Richard K. Talbot -- Architecture and social organization in the Fremont world / Lindsay D. Johansson -- Fremont ceramic designs and what they suggest about Fremont-ancestral puebloan relationships / Katie Richards.
Keywords: Indians of North America -- Southwest, New -- Antiquities -- Congresses; Indians of North America -- Southwest, New -- Social conditions -- Congresses; Social interaction -- Southwest, New -- Congresses; Group identity -- Southwest, New -- Congresses; Social archaeology -- Southwest, New -- Congresses; Excavations (Archaeology) -- Southwest, New -- Congresses